Different communities, different choices Human agency and the formation of tableware distribution patterns in Hellenistic Asia Minor - van der Enden, Mark (Journal of Greek Archaeology, 2016)
The interpretation of pottery distribution patterns has always been an important analytical endeavour in archaeological approaches to the past. The spatial distribution of pottery has, for example, been queried to identify cultural zones, landscape use, activity areas, and patterns of trade and economic interaction. Pottery distribution patterns can indeed tell us an awful lot about the socio-economic, cultural and geo-political dispositions of the past. Researchers of Classical Greek and Roman pottery have in particular made great strides in this respect and significantly increased our understanding of not only the pottery itself but also the way in which it was produced, distributed, used and discarded. What have not yet received much attention, however, are the formation processes lying behind ceramic distribution patterns observable in the archaeological record. It is precisely with this issue that the present contribution is concerned and by focussing on the Hellenistic tableware distributions of four archaeological sites in (Western) Asia Minor, it will test the importance and role of contextualized human agency with regards to the formation of ceramic distribution patterns.